(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The advent of progressive writings has been a new phenomenon that reflects the changes in the pre-independence Indian society to fight against the social evils. Realism aims at objectivity, psychological representation of characters and a search for truth in a matter of fact way. The development of imperial experience strikes the note of moral upheaval and confusion. The imperialists, despite their claims to be torch bearers of civilization, were exploiting the colonies for raw materials and income. The First World War exposed the hollowness of fake promises of the British Empire. The pre-independence writers wrote a literature of protest against the foreign government empowered with fatal weapons. They were rational and realistic in their approach towards life and developed the public taste for philosophy, science and other fields of knowledge. They worked as an example for progressive writers as it depicted the deterioration of elite class and backwardness of the society as a whole. Subject became more important than form so they conceived man as a crown of creation, capable of utilizing the natural objects to serve the interests. They believed in the self-respect of everyman. These concepts are the crux of progressive literature and exercised a great literature on the progressive writers. The old values collapsed and the new had not been yet born. The awakening of labour class and farmers strengthened. Like politicians, writers were also left with no choice except to choose the path to revolution or to quit the scene. They wrote about the oppressor and the oppressed and also depicted the problems of untouchables, middle and lower middle class illustrating their psychological state of mind, highlighting their suppressed desires, ignorance, narrow mindedness, superstitious nature and their exploitation due to corruption prevalent in the society.